2010
DOI: 10.1063/1.3386385
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent measurements of nitrous oxide and carbon dioxide collisional relaxation processes by a frequency down-chirped quantum cascade laser: Rapid passage signals and the time dependence of collisional processes

Abstract: Intrapulse quantum cascade laser spectrometers are able to produce both saturation and molecular alignment of the gas sample. This is due to the rapid sweep of the radiation through the absorption features. The intrapulse time domain spectra closely resemble those recorded in coherent optical nutation experiments. In the present paper, the frequency down-chirped technique is employed to investigate the nitrous oxide-foreign gas collisions. We have demonstrated that the measurements may be characterized by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…Furthermore, chirp times from a few μs down to a few tens of ns enable sensitive background-free detection of the free induction decays. Similar to that demonstrated in the mid-IR using cw [50] and pulsed quantum cascade lasers (QCL) [51,52,53,54], here we show that AWG driven EO-DOFCs can reach the chirp rates necessary to extend these MW/THz techniques to broad bandwidths in the near-IR [55,56,21] and beyond.…”
supporting
confidence: 81%
“…Furthermore, chirp times from a few μs down to a few tens of ns enable sensitive background-free detection of the free induction decays. Similar to that demonstrated in the mid-IR using cw [50] and pulsed quantum cascade lasers (QCL) [51,52,53,54], here we show that AWG driven EO-DOFCs can reach the chirp rates necessary to extend these MW/THz techniques to broad bandwidths in the near-IR [55,56,21] and beyond.…”
supporting
confidence: 81%
“…As our effective laser linewidth is expected to be similar to that achieved by Remillard et al 16 in their Lamb Dip experiment, about 4 MHz, we would not expect to see resolved spectra. In order to resolve this conundrum we will make use of several comparators available, the analysis of the role of FID and rapid passage in analysis of the patterns in the N 2 O spectrum, 7,9 the role of the ac Stark effect (Autler-Townes effect) 3 in determining the effective hyperfine splitting, and the difference in the signals recorded using the short and long pathlength cells. First, the analysis of the signals recorded using nitrous oxide 7,9 showed that rapid-passage effects, with scan rates much faster than the collision frequency, were the most effective in inducing large oscillatory signals when the scan direction was towards line centre, as it is in the present examples.…”
Section: Resultsmentioning
confidence: 99%
“…Within a pulse of duration 1.5 μsec the laser frequency can scan over 90 GHz (∼3 cm −1 ) to lower frequencies. [7][8][9] This is known as a frequency downchirp. As the duration of the interaction time of the laser radiation with an absorbing molecule may be very short, between 2 and 6 ns, the interaction time is shorter than the time between molecular collisions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations